Common bean as a potential crop for future food security: an overview of past, current and future contributions in genomics, transcriptomics, transgenics and proteomics. Issue 1 (1st January 2021) - Nadeem, Muhammad Azhar; Yeken, Mehmet Zahit; Shahid, Muhammad Qasim; Habyarimana, Ephrem; Yılmaz, Hilal; Alsaleh, Ahmad; Hatipoğlu, Rüştü; Çilesiz, Yeter; Khawar, Khalid Mahmood; Ludidi, Ndiko; Ercişli, Sezai; Aasim, Muhammad; et al.
Abstract: Common bean is an important legume crop having high quality protein, micronutrients, vitamins and antioxidants, which makes it a "grain of hope" for poor communities. Hence, a good number of breeding activities have been performed on the improvement of various key traits for years. However, recent advancements in molecular markers, sequencing technologies and the completion of the common bean genome sequence have opened numerous opportunities for fine mapping and gene characterization. The availability of these tools together with investigations of quantitative trait loci (QTL) and candidate genes for key traits such as morpho-agronomic, iron and zinc contents, cooking and quality traits, antioxidant activity, biotic and abiotic stresses pave the way to the development of new strategies for common bean genetic improvement. As a food source, it can contribute to the reduction of food scarcity worldwide in the coming years. Therefore, it is very important to take synergic efforts to integrate common bean genetic and genomic resources in breeding activities to ensure food security and contribute significantly to improved livelihoods in developing countries. Moreover, Kompetitive allele specific PCR (KASP) and CRISPR-Cas9 should be used to develop climate resilience common bean varieties. Here, we provide an overview of the evolution of common bean research by highlighting the past and recent advances in genomics, transgenics, transcriptomics and proteomics and also critically discuss the future prospects for further genetic improvement and better expansion of this crop.